Extrinsic coefficient charcterisation of PZT ceramics near the morphotropic phase boundary - Albareda, A.; Pérez, R.; García, J.; Tiana, J.; Pérez, E.; Gorri, J. A. (Boletín de la Sociedad Española de Cerámica y Vidrio, 2006)
PZT ceramics with high piezoelectric coefficients have high extrinsic contributions. This extrinsic behaviour, which is related to the domain wall movement, produces high non-linear effects that are sometimes inconvenient, for example when it increases the losses in power devices. The relation between extrinsic behaviour and non-linearities could be used to provide a good extrinsic characterization of materials in order to optimise the piezoelectric devices. In all cases the physical explanation of the behaviour is sought. The aim of this work is to study the dependence of the linear and non-linear dielectric, piezoelectric and mechanical coefficients on the Ti fraction in PZT ceramic compositions near the morphotropic phase boundary (MPB). The dependence of these coefficients on the defect concentration is also analysed. Hard ceramics belonging to Ferroperm Piezoceramics, with two different acceptor dopant levels, high and low, have been measured. Las cerámicas PZT con coeficientes piezoeléctricos elevados poseen contribuciones extrínsecas grandes. Este comportamiento extrínseco, relacionado con el movimiento de las paredes de los dominios, comporta efectos no lineales grandes que no siempre son deseables, por ejemplo, al incrementar las pérdidas de los dispositivos piezoeléctricos. Esta correspondencia entre efectos extrínsecos y no linealidades puede ser utilizada para caracterizar las cerámicas con el fin de optimizar sus propiedades piezoeléctricas. En todos los casos se busca una interpretación física de los resultados obtenidos. El objetivo de este trabajo es el estudio de la dependencia de los coeficientes lineales y no lineales dieléctricos, piezoeléctricos y elásticos con la fracción de Ti en cerámicas PZT con composiciones de Zr-Ti cerca de la transición de fase morfotrópica (MPB). También se analiza la dependencia de estos coeficientes con la concentración de impurezas, utilizando para ello cerámicas de Ferroperm Piezoceramics del tipo duras y con dos niveles de dopaje aceptor, alto y bajo.